Historicizing Life-Writing and Egodocuments in Early Modern Europe - Farr, James R.; Ruggiero, Guido (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This volume historicizes the study of life-writing and egodocuments, focusing on early modern European reflections on the self, self-fashioning, and identity. Life-writing and the study of egodocuments currently tend to be viewed as separate fields, yet the individual as a purposive social actor provides significant common ground and offers a vehicle, both theoretical and practical, for a profitable synthesis of the two in a historical context. Echoing scholars from a wide-range of disciplines who recognize the uncertainty of the nature of the self, these essays question the notion of the autonomous self and the attendant idea of continuous identity unfolding in a unified personality. Instead, they suggest that the early modern self was variable and unstable, and can only be grasped by exploring selves situated in specific historical and social/cultural contexts and revealed through the wide range of historical documents considered here. The three sections of the volume consider: first, the theoretical contexts of understanding egodocuments in early modern Europe; then, the practical ways egodocuments from the period may be used for writing life-histories today; and finally, a wider range of historical documents that might be added to what are usually seen as egodocuments.
1. Introduction - James Farr and Guido Ruggiero -- 2. The Elusive Self: An Essay - John Jeffries Martin -- 3. The Life Enhancing Value of Life-Writing: On the Uses and Disadvantages of History in Vasari's Lives of Artists - Douglas Biow -- 4. Benvenuto Cellini Magnanimously Corrects the Irritating Ignorance of Life Writers in General and in Regard to My Vita - Guido Ruggiero -- 5. Conversions and Crossing Frontiers: The Lives of Two Spanish Monks - James Ameland -- 6. Everard Nithard's Memoria: The Jesuit Confessor's Quest for Re-fashioning the Self, People and Events - Silvia Z. Mitchell - 7. Egodocument History and the Diary of Constantijn Huygens, Jr. - Rudolf Dekker -- 8. Dimensions of the Self in Autobiographical Life-Writing: James Boswell's Journals and William Hickey's Memoirs - James R. Farr -- 9. Our Letters, Our Lives: Self-Performance as Life-Writing in Italian Renaissance Correspondence - Deanna Shemek -- 10. Writing About the "Other" in One's Life: Life-Writing and Egodocuments of King Frederick William I of Prussia (1713-40), Frederick II of Prussia, and Wilhelmina of Bayreuth - Benjamin Marschke -- 11. A Dutch Notary and His Clients - Mary Lindemann -- 12. The Genres and Modes of Early Modern Women's Life-Writing: Anne Clifford and Anne Marie Louise d'Orleans - Mihoko Suzuki.
Keywords: Civilization-History.; Europe-History-1492-.; Literature-History and criticism; Cultural History; History of Early Modern Europe; Literary History